THE LEGAL CONSEQUENCES OF A COOPERATION AGREEMENT DUE TO MERGER - Zulfikar Muhammad Rafif (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2022)
Cooperation agreement is a bond between one party and another party to bind themselves in doing or not doing something in particular. Basically, the agreement creates rights and obligations by the parties and is regulated in the Civil Code. Companies when running their business often carry out corporate actions aimed as a way to survive and to increase company profits, one of which is by merging the company. Mergers are often used apart from the relatively low cost, the methods and mechanisms that are carried out are simpler so that they become more efficient. Research methods used in writing this paper is a normative juridical method. Often problem arise in mergers are doubts and uncertainties in determining the legal consequences of an agreement, including cooperation agreement with third parties that were made prior to the merger. The legal consequence of a merger is the company’s assets and liabilities are transferred directly without going through a liquidation process. If during the merger, one of the companies is still bound by a cooperation agreement with a third party, then the rights and obligations contained in the cooperation agreement are transferred by law without needed a deed of transfer to delivered these rights and obligations.